Impact of Knowledge Creation and Sharing on Knowledge Use Among Librarians in Federal Universities in Nigeria - Ogunmodede, Thomas; Popoola, Sunday Olanrewaju (International Journal of Knowledge Content Development & Technology, 2024)
This paper aims to determine the impact of knowledge creation and sharing on use by librarians in federal universities in Nigeria. The study adopted the survey method of the correlation type, where 518 librarians were surveyed through a close-ended questionnaire, descriptive statistics, Pearson Product Moment Correlation coefficient and multiple regression were used to test the hypotheses. Findings indicate that significant relationships exist between knowledge creation and knowledge sharing (r=0.52), knowledge sharing and knowledge use (r=0.63) and knowledge creation and knowledge use (r=0.52), respectively. Knowledge created and shared by the librarians is used for better work performance. The paper adds value to the existing body of knowledge by proposing the need to understand the importance of knowledge creation and sharing as facilitators of knowledge use by librarians. This will, in turn, enhance service delivery to library patrons, thereby improving library patronage. This paper is limited to knowledge creation and sharing and its impact on knowledge use. Types of knowledge created and channels through which knowledge is shared are outside the focus of this article.